The Effect of Auditor Ethics and Auditor Professional Skepticism on Audit Quality with Remote Audit as a Moderation Variable - Julianti, Pujihastuti Dwi; Muhyarsyah, Muhyarsyah (Journal of Social Research, 2023)
The increasing demand for professional public accounting services requires the public accounting profession to improve its performance to produce audits that are reliable, used, and trusted by interested parties. This study aims to identify and analyze the effect of auditor ethics and professional skepticism on audit quality with remote audit as a moderating variable. This study uses primary data obtained from questionnaire data distributed to external auditor respondents who work at a Public Accounting Firm in the South Jakarta Region. The sampling technique used purposive sampling. Multiple linear regression analysis techniques using SmartPLS 3.2.9 with a significance level of 5%. The results of this study indicate that partially, auditor ethics and auditor professional skepticism have a positive and significant effect on audit quality, while remote audit variables cannot moderate the influence between auditor ethics and auditor professional skepticism on audit quality.